2020
DOI: 10.1186/s13567-020-00772-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal thyroid dysfunction following porcine reproductive and respiratory syndrome virus2 infection

Abstract: To better understand the host response to porcine reproductive and respiratory virus-2 (PRRSV2) we evaluated circulating thyroid hormone and associated gene expression in a late gestation challenge model. Pregnant gilts were inoculated at gestation day 85 and fetal samples collected at either 12 or 21 days post-infection (dpi). A subset of fetuses was selected for analysis based on viability and viral load categorized as either uninfected-viable (UNIF), high viral load viable (HV-VIA) or high viral load meconi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 66 publications
5
32
0
Order By: Relevance
“…The question of PRRSV infection in the fetus as the cause of demise has been previously questioned based on the understanding that fetal lesions are infrequently observed [ 19 ]. However, it is now understood that the fetus responds physiologically and immunologically to PRRSV infection in the absence of pathology [ 11 , 13 , 14 , 45 ]. Previous reports show a positive association between fetal survival during PRRSV infection and reduced intrauterine growth [ 16 ], of which increased apoptosis and increased cellular senescence could contribute to reduced fetal growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question of PRRSV infection in the fetus as the cause of demise has been previously questioned based on the understanding that fetal lesions are infrequently observed [ 19 ]. However, it is now understood that the fetus responds physiologically and immunologically to PRRSV infection in the absence of pathology [ 11 , 13 , 14 , 45 ]. Previous reports show a positive association between fetal survival during PRRSV infection and reduced intrauterine growth [ 16 ], of which increased apoptosis and increased cellular senescence could contribute to reduced fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of fetal demise is not well understood with debate on whether activities at the MFI (maternal endometrium and/or fetal placenta), activities in the fetus, or both are responsible, and to what degree [ 7 ]. Studies using gene expression have found common themes during fetal infection with PRRSV including changes in innate and adaptive immunity, hypoxia, interferon signaling, apoptosis, and thyroid hormone dysregulation [ 11 14 ]. Our current study is part of the largest set of studies to date using the pregnant gilt challenge model to understand phenotypic and genotypic responses to PRRSV infection in fetuses and gilts [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In short, total RNA was extracted and viral RNA quantified using primer and probe sequences targeting the distal region of ORF7 and a one-step qPCR assay including a standard curve comprised of linearized plasmid. Fetal serum thyroid hormone levels (T3 and T4) were each evaluated using commercially available RIA as previously described [ 15 ]. For initial evaluation, the resulting data on viral load and thyroid hormone level was used in combination with meconium staining to identify subsets of fetuses from the larger population produced by the challenge model that represent four biologically distinct, and physiologically extreme groups.…”
Section: Methodsmentioning
confidence: 99%
“…This growth is driven by progressive increases in growth promoting signals such as insulin-like growth factor 1 [ 13 ], and thyroid hormones [ 14 ] including thyroxin (T4) and its more bioactive derivative triiodothyronine (T3). Although the PRRSV infected fetus is capable of mounting an immune response [ 6 , 8 ], it creates not only supplemental energetic cost but results in a cytokine response that may interfere with normal developmental processes, including a significant disruption in fetal thyroid hormone levels [ 15 ]. Moreover, type I and II interferons, which are elevated following fetal PRRSV expression [ 6 ], have a detrimental impact on placental and fetal development and are implicated in intrauterine growth restriction (IUGR) in other models of congenital infection [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation